Concurrently Oral Candidiasis and Oral Hairy Leukoplakia (OHL) As a Clinical Predictive of HIV infection - Priandini , Dewi (Jurnal Kedokteran Gigi Terpadu, 2022)
Introduction Acquired immunodeficiency syndrome (AIDS) present oral manifestations such as oral candidiasis (erythematous and pseudomembranous), oral hairy leukoplakia (OHL). The presence of oral candidiasis and OHL within the oral cavity not only suggests HIV infection, but is possibly one of the first signs of development into AIDS in the HIV-infected individual Case Presentation A 26 -year -old female reported to the Dental Hospital of Faculty Denstistry of Trisakti University with complaint of burning sensation and oral discomfort, altered taste at the tongue from the past since 6 months. Intra Oral examination revealed white lesion at dorsal of the tongue and red lesion at the middle of the tongue and also vertical white lesion looks like a plague at the ventral of the tongue . Conclusion Oral candidiasis is one of the most common, seen in persons with HIV or AIDS . The oral health status of an HIV-infected patient at presentation is an extremely important parameter. Very important to verify whether there is a relationship between the presence of OHL and clinical characteristics of the patients.